2015
DOI: 10.1103/physrevd.92.124056
|View full text |Cite
|
Sign up to set email alerts
|

Brans-Dicke cosmology does not have theΛCDMphase as a universal attractor

Abstract: In this paper we seek for relevant information on the asymptotic cosmological dynamics of the Brans-Dicke theory of gravity for several self-interaction potentials. By means of the simplest tools of the dynamical systems theory, it is shown that the general relativity de Sitter solution is an attractor of the Jordan frame (dilatonic) Brans-Dicke theory only for the exponential potential U (ϕ) ∝ exp ϕ, which corresponds to the quadratic potential V (φ) ∝ φ 2 in terms of the original Brans-Dicke field φ = exp ϕ,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 83 publications
(234 reference statements)
1
17
0
Order By: Relevance
“…J 4 represents an accelerating solution with w tot = −1. At the end of section 2.3 we will discuss on the corresponding asymptotics giving new arguments supporting the statements in [26] against [19][20][21]. Indeed, J 4 represents an intermediate solution at late time, i.e., a(t) ≃ e α 1 t p 1 as t → ∞ where α 1 > 0, and…”
Section: J 3 Is a Scaling Solution Between ω Effmentioning
confidence: 88%
See 1 more Smart Citation
“…J 4 represents an accelerating solution with w tot = −1. At the end of section 2.3 we will discuss on the corresponding asymptotics giving new arguments supporting the statements in [26] against [19][20][21]. Indeed, J 4 represents an intermediate solution at late time, i.e., a(t) ≃ e α 1 t p 1 as t → ∞ where α 1 > 0, and…”
Section: J 3 Is a Scaling Solution Between ω Effmentioning
confidence: 88%
“…Summarizing, we have explicitly shown that the solutions near J 4 satisfy Φ ∼ 1 t p 1 , ΦR ≃ At p 1 −2 + Bt −2 and H ≃ α 1 p 1 t p 1 −1 , which tend asymptotically to zero but never reach this value. Besides, the effective gravitational coupling (the one measured in Cavendish-like experiments) [26],…”
Section: Viability Of the Intermediate Accelerated Solution In The Jomentioning
confidence: 99%
“…Studies of scalar-tensor theories have been performed by one of the present authors using these techniques [14,16], and similar and complementary analysis can be found in the literature that followed [18,19,30,31,33,34]. Some of these works focus their analysis to the case of Brans-Dicke theory [30,33,34], while others investigations consider more general scalar-tensor theories.…”
Section: Scalar-tensor Gravity Theoriesmentioning
confidence: 75%
“…The qualitative behaviour depicted in Figure 3 reveals that with the exception of the oscillatory solutions, confined to a closed patch, all other solutions emerge from a collapsing deS solution at X = ∞, X = −∞ and end in the deS solution at X = ∞, X = +∞, thus revealing the domination of the cosmological potential term [14,30,[32][33][34]38,39]. More importantly, we see that the solutions are attracted to the positive G half plane.…”
mentioning
confidence: 84%
“…However, we think that this very important subject needs to be discussed in more length. We want to make clear that the statement on the non-universality of the GR-de Sitter equilibrium point, 454 does not forbids the possible existence of exact de Sitter solutions for several choices of the self-interaction potential (see, for instance, Ref. 467).…”
Section: (Non)emergence Of the λCdm Phase From The Brans-dicke Cosmologymentioning
confidence: 99%